2014
DOI: 10.1007/s13187-013-0585-7
|View full text |Cite
|
Sign up to set email alerts
|

Knowledge and Fears Among Asian Americans Chronically Infected with Hepatitis B

Abstract: Asian Americans are disproportionately affected by hepatitis B (HBV) infection. In the USA, one in ten Asian Americans is infected with HBV. The purpose of the study was to explore knowledge, fears and follow-up care among Asian Americans chronically infected with hepatitis B. A sample of 154 completed an online survey which included demographic information, follow-up treatment information, and HBV knowledge and fears/concerns. Our findings indicate that there are differences by ethnicity and birthplace among … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

7
52
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(59 citation statements)
references
References 16 publications
7
52
0
Order By: Relevance
“…Similar to other studies, hepatitis B patients had the fear of infecting their loved ones in addition to fear of liver cancer and their lives being threatened by the disease (33).…”
Section: Discussionsupporting
confidence: 72%
“…Similar to other studies, hepatitis B patients had the fear of infecting their loved ones in addition to fear of liver cancer and their lives being threatened by the disease (33).…”
Section: Discussionsupporting
confidence: 72%
“…[39] Fear of HBV infection is the most common cause of HBV stigma. [242733353843] A lack of knowledge and awareness of HBV often resulted in a misunderstanding of the disease and results in the stigmatization of one's own self or stigmatization of people infected with HBV. [15242728293241] The findings of both quantitative and qualitative studies revealed that most Asian or Asian Americans including health-care providers stated that sharing of contaminated food and eating utensils was the most common route of HBV transmission.…”
Section: Resultsmentioning
confidence: 99%
“…Other hepatitis B-related fears and concerns have also been reported among people with CHB in several other studies (3, 5, 10, 13, 17-19, 21-23) with these psychological stressors possible predisposing factors to developing psychiatric disorders, particularly depressive disorders. In one study among people with CHB, having hepatitis B-related concerns were associated with the presence of major depression (3).…”
Section: Discussionmentioning
confidence: 57%